The Dilemma Of The Baduy Legal Community Facing The Challenge Of Traditional Values Amidst Of Legal And Globalization - Yenny Febrianty; Nadya Restu Ryendra (Eduvest - Journal of Universal Studies, 2024)
The Baduy Indigenous Community is reluctant to accept external influences, including technology and knowledge, which has led them to live in isolation from the advancements of time and modernization due to their customary norms that prohibit members from interacting with technology, including the internet. This research aims to understand the dilemma faced by the Baduy Indigenous Community in preserving their traditional values amid the dynamics of law and globalization. The method employed is qualitative descriptive research. Data collection is conducted through observation, documentation, and interviews with the Baduy community and local residents. The research findings indicate that, in facing the dynamics of law and global trends, the Outer Baduy community undergoes transformation and has adapted to communication technology and gradually accepted global influences. In contrast, the Inner Baduy tribe remains committed to tradition as the inheritors of their Indigenous Culture, thus rejecting change and globalization. However, they face challenges due to the growth of the tribe's members that is not proportionate to their arable land. Concerns about environmental changes and the impact of globalization have entrapped them in a dilemma. Therefore, it is important to recognize that culture is inherently dynamic and evolving.